Importance of Cheese Whey Processing: Supplements for Sports Activities – a Review - Patricia Fassina; Gabriela Quadros Nunes; Fernanda Scherer Adami; Márcia Inês Goettert; Claucia Fernanda Volken de Souza (Polish Journal of Food and Nutrition Sciences)
Whey protein (WP) is a highly nutritious, commercially available alternative food source that is used primarily as a food supplement by athletes and physically active individuals to provide them with essential amino acids and bioactive peptides, and additional benefits have been attributed to WP consumption. In this context, the objective of this review was to explore current evidence regarding the consumption of different WP supplements in sports nutrition to elucidate their efficiency in affecting muscle hypertrophy, physical performance, response to muscle injury, weight loss, and body composition changes. Furthermore, these effects were assessed by comparing whey protein hydrolysate (WPH), whey protein concentrate (WPC), and whey protein isolate (WPI) supplementation. Supplementation with WPI or WPC was related to increased muscle protein synthesis (MPS), and WPH caused muscle hypertrophy and improved physical performance. Compared to WPC and WPI, WPH improved peak torque associated with strength training without reducing the creatine kinase (CK) and tumor necrosis factor alpha (TNF-α) levels in this type of physical activity, and the decreases in CK and lactate dehydrogenase (LDH) associated with aerobic exercise were significant. Supplementation with WPC resulted in weight loss, satiety and improved body composition, without compromising whole-body lean mass loss. WPH was more effective than WPC and WPI regarding improved peak torque and muscle hypertrophy associated with strength training, and WPH reduced muscle damage associated with aerobic exercise via decreased CK levels.